2022
DOI: 10.7759/cureus.22979
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Gestational Diabetes Mellitus Among Saudi Women in a Primary Health Care Center of Almadinah Almunawarah, Kingdom of Saudi Arabia

Abstract: BackgroundGestational diabetes mellitus (GDM) is a type of diabetes mellitus known as any stage of glucose intolerance with onset or first recognition during pregnancy. Awareness of GDM is the first step toward its screening in pregnancy. This study was designed to assess knowledge of GDM, its screening, and risk factors among Saudi women attending primary healthcare center in Almadinah Almunawarah, Kingdom of Saudi Arabia. MethodsThis was an observational cross-sectional study conducted on Saudi women who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…(2020) involving 292 Saudi women in Almadinah Almunawarah, which utilized a valid Arabic self-administered questionnaire. [ 28 ] One possible explanation for this discrepancy could be the availability of greater health education resources in urban areas, which may contribute to higher levels of HL.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) involving 292 Saudi women in Almadinah Almunawarah, which utilized a valid Arabic self-administered questionnaire. [ 28 ] One possible explanation for this discrepancy could be the availability of greater health education resources in urban areas, which may contribute to higher levels of HL.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, it is noteworthy that 316 (65.6%) had good knowledge about GDM. Inversely, a crosssectional study conducted in Almadinah Almunawarah, Saudi Arabia, among women attending primary healthcare centers found that over half of the participants (n=178, 53.45%) had a poor level of knowledge about GDM, while only 7.80% (N=26) possessed a good level of knowledge on the subject [11].…”
Section: Discussionmentioning
confidence: 99%
“…Females below the age of 18 years, living outside the Qassim region, and those with intellectual disabilities were excluded from the study. A validated questionnaire was provided and approved by the authors of a study conducted in Al Madinah Province in 2022 [ 10 ]. Additional questions were added to ensure comprehensiveness and improve validity.…”
Section: Methodsmentioning
confidence: 99%
“…In the study conducted in Al Madinah, the authors reported the prevalence of gestational diabetes as poor knowledge in their study to be 53.45% [ 10 ]. The same prevalence, a 95% confidence interval, and an absolute precision (alpha) of 5% were adopted in the present study to calculate the sample size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation